Answer:
y - x = 16
Explanation:
Explanation:-
Step(i):-
Given data set A is 9,5,y,2,x
Mean of the Data set A
=
![(9 + 5 + y + 2 +x)/(5)](https://img.qammunity.org/2021/formulas/mathematics/college/fnhymiaf72cly1hl5tj9pu5debcnto2hqq.png)
=
![(16 +x+y)/(5)](https://img.qammunity.org/2021/formulas/mathematics/college/2m4rmbrxfr7hiid8v1bk9larc7lf82b1nx.png)
Given data set B is 8, x, 4, 1, 3
Mean of the Data set B
=
![(8+ x+4+1+3)/(5)](https://img.qammunity.org/2021/formulas/mathematics/college/lxeocr021ffai4x105hq07ly0ne5ws2u87.png)
Step(ii):-
Mean of the Data set A = 2 X Mean of the Data set B
![(16 +x+y)/(5) = 2 X (16+x)/(5)](https://img.qammunity.org/2021/formulas/mathematics/college/siko1wel9qzw1ma6grkler9bs992juu6d8.png)
On simplification , we get
16 +x + y = 2( 16 +x)
16 + x + y = 32 + 2 x
16 + x + y - 32 - 2 x = 0
y - x -16 =0
y - x = 16